Management of haemorrhoid in a tropical .country (2004)
To appraise the pattern of presentation and management of Haemorrhoids in Ile-Ife. Setting: State Hospital and Wesley Hospital, Ilesa 2 major units of Obafemi Awolowo University Teaching Hospital Complex, Ile-Ife, Osun State, Nigeria. Design: Retrospective Study. January 1990 to December, 2001 Patients and Method. 70 patients who presented with prolapsed (second and third degrees), over 11 years period were studied. Results Age Range was 10-80 years (average 27.8 + 1.9) with a male preponderance. Sixty-seven percent had prolapsing pile; 61.4% had open .excisional haemorrhoidectomy. Conclusion: It is felt that the late presentation was mainly due to fears, false belief and quackery often associated with the disease and its treatment. It was therefore suggested that more effort be made towards education of population in other to reduce above problems and encourage early presentation so that less invasive costly techniques could be used.